Theory-informed strategies to address factors anticipated to influence implementation and people's participation in community pharmacy-based diabetes prevention services - Thando Katangwe-Chigamba; Jeremy Sokhi; Hannah Family; Hiyam Al-Jabr; Charlotte L. Kirkdale; Michael J. Twigg (Elsevier, 2023)
Background: Early identification of non-diabetic hyperglycaemia and implementation of diet and lifestyle changes can prevent type 2 diabetes. However, low participation in diabetes prevention services remains a problem in the UK. The community pharmacy, one of the most accessible healthcare settings in the UK, could provide one solution to improving participation. Aim: To prioritize factors that could influence delivery of, and people-participation in, community pharmacy-based diabetes prevention services, and to identify strategies to facilitate successful implementation. Methods: A mixed-methods, primary care-based study, comprising of two stages: 1- Prioritizing key influences of participation and delivery using a structured Nominal Group Technique with people with non-diabetic hyperglycemia, and other stakeholders; 2 - Identifying theory informed strategies to facilitate successful implementation using framework analysis. This involved mapping prioritized influences and qualitative data from the Nominal Group Technique onto the Behaviour Change Wheel theoretical framework. The study was conducted in February 2019, in Norfolk, UK and ethical approval obtained prior to research commencing. Results: Fifteen participants (five people with non-diabetic hyperglycaemia, nine community pharmacy and general practice staff and one commissioner) participated. Participants prioritized "awareness" and "service integration" as key factors likely to influence participation and "the provision of information about health consequences e.g., leaflets" and "action planning e.g. general practice referral of patients to prevention services" as key strategies to facilitate participation. "Training", "staffing levels" and "workload" were amongst the key factors prioritized as most likely to influence delivery. Strategies identified to facilitate implementation included "instructions of how to perform the behaviour e.g. standard operating procedures" and "reward e.g. funding". Conclusions: This research provides theory informed strategies needed to facilitate successful implementation of community pharmacy-based diabetes prevention services. The findings of this study should inform the design of future diabetes prevention services to ensure participation and sustainability.